Implicaciones de la calidad de vida en las decisiones quirúrgicas del cáncer de pulmón - Puente-maestu, Luis; Villar, Felipe (Psicooncología, 2006)
Available evidence suggests that the patients with a forced expiratory volume in 1 second [FEV1] over 60% or in which a postoperative FEV1 is predicted over 45%, they do not develop severe disability after lung resection surgery; nevertheless, currently some groups are operating patients with EPOC and FEV1 less than 35%. In emphysema patients can occur that the function improve, as in the volume reduction lung surgery, but in the cases that it does not occur, they can remain with chronic shortness of breath until a 10%. At present, there are not any functional or effort test that be able to predict what patients will present satisfactory residual pulmonary function or chronic shortness of breath or important exercise limitations. It has been noticed that medical team opinion is not satisfactory to predict defi cit in postoperative quality of life. Nevertheless, long-term survivors (more than one year) inform relatively good quality of life, even in which they have pulmonary function reduced. In comparison with other chronic respiratory diseases, the survivors of lung cancer seem to be in better psychological state, the defi cit in quality of life is caused mainly by depression, and not for physical limitation. Therefore, empirical evidence does not justify excluding undergoing surgery on basis of medical team suppositions about a postoperative poor Quality of life. In addition, studies about Quality of Life suggests patients who is undergo lung cancer surgery are willing to assume risks for their survival, although, they want to receive information about how surgery may affect them.